Symbiont Genomic Features and Localization in the Bean Beetle Callosobruchus Maculatus - Ko'bayev Juradek Eshmamatovich; Xidirova Sayyora Akbar qizi (Scientific Trends, 2024)
A pervasive pest of stored leguminous products, the bean beetle Callosobruchus maculatus (Coleoptera: Chrysomelidae) associates with a simple bacterial community during adulthood. Despite its economic importance, little is known about the compositional stability, heritability, localization, and metabolic potential of the bacterial symbionts of C. maculatus. In this study, we applied community profiling using 16S rRNA gene sequencing to reveal a highly conserved bacterial assembly shared between larvae and adults. Dominated by Firmicutes and Proteobacteria, this community is localized extracellularly along the epithelial lining of the bean beetle’s digestive tract. Our analysis revealed that only one species, Staphylococcus gallinarum (phylum Firmicutes), is shared across all developmental stages. Isolation and whole-genome sequencing of S. gallinarum from the beetle gut yielded a circular chromosome (2.8 Mb) and one plasmid (45 kb). The strain encodes complete biosynthetic pathways for the production of B vitamins and amino acids, including tyrosine, which is increasingly recognized as an important symbiont-supplemented precursor for cuticle biosynthesis in beetles. A carbohydrate-active enzyme search revealed that the genome codes for a number of digestive enzymes, reflecting the nutritional ecology of C. maculatus. The ontogenic conservation of the gut microbiota in the bean beetle, featuring a “core” community composed of S. gallinarum, may be indicative of an adaptive role for the host. In clarifying symbiont localization and metabolic potential, we further our understanding and study of a costly pest of stored products.
Keywords: Host-microbe, symbiosis, bean beetle, insect, herbivory.